"Illiberal Democracy" in a Central European Country. Issue 2 (4th May 2019) - Ritter, Andrea
Abstract : The American election and its results in 2016 made it timely to provide a psychoanalytic analysis of the similar political events in the United States and in Hungary. Applying psychoanalytical theories to society has always been part of the tradition of the Budapest school. This paper argues that Hungarian and other transgenerational trauma theories can help us understand these developments. The author begins in using these theories to analyze the impact of political regimes on societies and individuals in Central Europe after World War II. She then continues to look at the political transformation that took place in 1989 in the socialist countries existing since 1945. This transformation promised liberation. But, this paper argues, the unexplored past resulted in the emergence of hierarchic, irrational political forces. The paper uses social and individual examples to help demonstrate these processes.